Manajemen Pemasaran Ekonomi Kreatif Untuk Meningkatkan Pendapatan Produk UMKM Singkong Jelaku - Janah, Uzlifatul; Ariyanti, Ovi (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2024)
The concept of creative economy, introduced by John Howkins, highlights the importance of creative ideas in transforming environmental materials into additional economic value, thereby enhancing welfare through job creation. Effective management, especially in SMEs, is crucial in ensuring business success with innovative marketing strategies. This research explores the potential of modified cassava flour (mocaf) as a healthy and economical alternative, emphasizing the need for creative production techniques and marketing management to increase SME revenue. The aim of this study is to understand product management and creative ideas in enhancing economic value by creating job opportunities. The research employs a qualitative descriptive approach and semi-structured interviews to analyze the case study of Punggelan Ribug village, which produces mocaf as its flagship product. Effective product and marketing management strategies, such as ensuring the quality of raw materials and implementing digital marketing, are essential to enhance visibility and sales. Mocaf has the potential as an environmentally friendly and gluten-free alternative to wheat flour, with fermentation process also reducing production costs. With emphasis on creative management and marketing, this research underscores the importance of innovation in increasing SME revenue and reaching a broader market.